2013
DOI: 10.1542/peds.2012-1092
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and 3-Year BMI Change in Overweight and Obese Children

Abstract: Sustained increase in moderate-vigorous PA predicts reducing BMI z score over 3 years in overweight/obese children presenting to primary care. However, the small BMI change associated with even the largest activity changes may explain disappointing BMI outcomes of brief primary care interventions targeting PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
3
32
1
1
Order By: Relevance
“…Other studies also have found BMI z-score decreased after participation in community-based physical activity and nutrition interventions [31,37]. We did not find a relationship between changes in MVPA and changes in BMI z-scores which may be due to the relatively small changes in MVPA and to the relatively short duration of SCFFF intervention.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Other studies also have found BMI z-score decreased after participation in community-based physical activity and nutrition interventions [31,37]. We did not find a relationship between changes in MVPA and changes in BMI z-scores which may be due to the relatively small changes in MVPA and to the relatively short duration of SCFFF intervention.…”
Section: Discussioncontrasting
confidence: 83%
“…There was moderate intervention effect (d=0.4) in the percentage of time spent in MVPA (1.1%), which is comparable to previous studies [36,37]. However, it is difficult to directly compare this study with others due to use of different cut points for MVPA [37] and devices [36].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…From the study of the research work, based on the performance of motor preschoolers' skills, it was found that there are few reports in the international scientific area and almost non-existent in Greece and those existed are associated with another variable such as the Body Mass Index [27][28][29][30][31], physical activity [21], social skills [1,[32][33][34][35] and developmental disorders of neuromuscular splice [15,36,37].…”
mentioning
confidence: 99%